Implementation of Thariqatul Mubasyarah with Video Media to Improve the Maharah of Kalam at STEI Hamzar East Lombok - Muh Ariadi Muslim (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
One of the methods used in learning Arabic is the direct method (Thariqatul Mubasyarah). The direct method is an approach to presenting foreign language material in which the teacher directly uses the target language as the medium of instruction without resorting to the students’ native language during language learning activities. To support the direct method (Thariqatul Mubasyarah) and make Arabic language learning more engaging, video media was utilized. The purpose of this study was to implement the steps of the direct method using video media to improve speaking skills. This study employed a descriptive qualitative research model, a type of research aimed at describing something in detail. Descriptive qualitative research utilizes data collection methods such as interviews, observations, and document analysis. As a result, students were able to speak Arabic fluently because they had prepared the conversations in advance. If they made a mistake, they repeated the segment until they spoke fluently and with the correct intonation. The challenges in applying the direct method included an environment that was not conducive to learning, difficulty memorizing the script quickly which required repeating the recording multiple times and a lack of confidence when appearing on camera. All these challenges could be overcome by getting accustomed to the process through repeating the recording four to five times. This study focuses solely on the direct method